Cross‐sectional clinical cancer genomics community of practice survey analysis of provider attitudes and beliefs regarding the use of deceased family member tissue to guide living family member genetic cancer risk assessment. Issue 5 (26th May 2022) - Nehoray, Bita; Slavin, Thomas P.; Sun, Can‐Lan; Hurley, Karen; King, Elisabeth; Tsang, Kevin K.; Cervantes, Aleck; Mokhnatkin, Janet V.; Sand, Sharon; Mejia, Rosa; Reb, Anne; Samimi, Goli; et al.
Abstract: Next‐generation tumor tissue sequencing techniques may result in the detection of putative germline pathogenic variants (PVs), raising the possibility that germline cancer predisposition could be identified from archival medical tissue samples of deceased relatives. The approach, termed traceback, is designed to inform risk management recommendations for living family members. Provider perspectives regarding traceback testing have not yet been explored, so we conducted a cross‐sectional survey of Clinical Cancer Genomics Community of Practice providers regarding their attitudes and beliefs toward traceback testing. Self‐reported demographics, provider characteristics, attitudes and perceived barriers were collected. We evaluated responses in the context of whether providers had previous experience with traceback testing. Data were analyzed using chi‐square and Fisher's exact testing. Among 207 respondents (of 816 eligible), most were women (89.4%), white (85.5%), and not Hispanic or Latino (89.7%). US‐based providers represented the majority of respondents (87.4%). Relatively, few providers 32 of 207 (15.5%) had previous experience with traceback. Among the individuals without experience in traceback, 84.0% thought there would be barriers to implementation; however, only 68.8% of individuals with previous traceback experience agreed ( p  = .04). Respondents in both groups thought that traceback would be valuable in their practice (82.6%, p  = .22) and that they would feel comfortable discussing the concept (83.6%, p  = .83), interpreting the results (72.2%, p  = .24), and discussing the results with their patients (80.7%, p  = .38). Patient interest and cost were seen as less of a barrier by those with experience with traceback testing. Recurrent themes obtained in open‐ended responses are also presented. Overall, providers believe that traceback would be a valuable tool in their practice. Individuals with previous experience identified less barriers with implementation of this testing, highlighting an area for future research and education.